THE DETERMINATION OF THE SERVICE LIFE OF BEARING STRUCTURES ROLLING STOCK USING THE TECHNIQUE OF COMPARING THEIR DYNAMIC WORKLOAD - Bondarev, O. M.; Gorobets, V. L.; Gruschak, I. M. (Science and Transport Progress, 2008)
In the paper on the example of electric trains of a series ЕР9 it is suggested a variant of estimation of service life for carrying structures of the motor-wagon rolling stock, which are analogs, on the basis of results of comparative analysis of values, measured experimentally in operation conditions, that characterize their loading conditions and stressed-and-strained state.